2009
DOI: 10.1007/s10067-009-1252-6
|View full text |Cite
|
Sign up to set email alerts
|

No association of the TLR2 gene Arg753Gln polymorphism with rheumatic heart disease and Behçet’s disease

Abstract: Behçet's disease (BD) is a multisystem inflammatory disorder of unknown etiology, and infections with different microorganisms including streptococci have been claimed as triggers of inflammatory attacks in BD pathogenesis. Toll-like receptor 2 (TLR2) has been known to recognize several microbial antigens including that of streptococci, and TLR2 gene Arg753Gln polymorphism has been reported to be strongly associated with acute rheumatic fever with an odds ratio of 100. This study aimed to investigate the TLR2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 15 publications
0
6
0
1
Order By: Relevance
“…TLR2 genine ait Arg753Gln ve Arg677Trp olmak üzere iki fonksiyonel polimorfizm tanımlanmıştır (65). Behçet hastalarının TLR tarafından algılanan streptokokus ve mikoplazma gibi infeksiyon ajanlarına yatkın olmasından yola çıkılarak TLR2 Arg753Gln polimorfizmi ile BH arasında ilişki olup olmadığı araştırılmış fakat herhangi anlamlı bir ilişki bulunamamıştır (66,67).…”
Section: Toll-like Reseptörunclassified
“…TLR2 genine ait Arg753Gln ve Arg677Trp olmak üzere iki fonksiyonel polimorfizm tanımlanmıştır (65). Behçet hastalarının TLR tarafından algılanan streptokokus ve mikoplazma gibi infeksiyon ajanlarına yatkın olmasından yola çıkılarak TLR2 Arg753Gln polimorfizmi ile BH arasında ilişki olup olmadığı araştırılmış fakat herhangi anlamlı bir ilişki bulunamamıştır (66,67).…”
Section: Toll-like Reseptörunclassified
“…Probably the most investigated TLR2 polymorphism is the 2258GϾA polymorphism, which in studies performed with European populations has been reported to be associated with several important infections, such as Candida infections (20), severe bacterial infections (31), late-stage Lyme disease (46), acute rheumatic fever (6), urinary tract infections (51), tuberculosis (36), and autoinflammatory diseases such as Behcet disease (13) and familial Mediterranean fever (37). The TLR2 2258GϾA SNP was also reported to be involved in the development of arthritis and extraarticular features following infection with Salmonella en- terica serovar Enteritidis (57).…”
Section: Discussionmentioning
confidence: 99%
“…111,118,119 Studies have also found associations between small ubiquitin-like modifier 4 (SUMO4) polymorphisms with Behçet disease 112,120 and C677T polymorphism in the 5,10-methylenetetrahydrofolate reductase (MTHFR) gene with ocular involvement in Behçet disease. 128 Researches have also investigated other candidate genes with function-based hypothesis, such as toll-like receptor 2 (TLR2), 129 protein tyrosine phosphatase non-receptor 22 (PTPN22), 130 endothelial nitric oxide synthase (eNOS), 131 and programmed cell death 1 (PD-1) genes. These included MEFV (the gene responsible for familial Mediterranean fever, FMF), 121 platelet glycoprotein receptor IIIA (GpIIIa) gene, 122 signal transducer and activator of transcription 3 (STAT3), 123 CD40, 124 IkappaBalpha, 125 cytotoxic T-lymphocyte antigen-4 (CTLA-4), 126 toll-like receptor-4 (TLR4), 127 and Fc receptor-like 3 gene (FCRL3).…”
Section: Other Genes Implicated In the Development Of Uveitismentioning
confidence: 99%